Foreign direct investment openness and income classes in Europe around the great recession. - Arestis, Philip; Bárcena-Martín, Elena María; Martín-Fuentes, Natalia; Pérez-Moreno, Salvador Jesús (Taylor & Francis, 2023)
Distributional implications of capital account regulation is eminently context-specific. This paper examines the distributional effects of the openness of foreign direct investment (FDI) flows across 27 European countries in different economic environments around the Great Recession, covering the period 2007–2013. Our multi-level approach allows us to combine country-level variables and sociodemographic characteristics of individuals. The results highlight that the openness of FDI flows heterogeneously affects the income share of individual groups, favouring in particular the highest income classes. This finding seems to be driven by the educational level. We argue that even though highly educated individuals are present along the entire distribution, the highest income classes are especially favoured by the openness of FDI flows. This biased distributional effect of the openness of FDI flows persists throughout the years examined, regardless of the economic environment; this is due, in part, to the fact that the distribution of highly educated people is not sensitive to the business cycle.
Keywords: Distribución de la renta; Inversiones extranjeras; Modelos multinivel (Estadística); Foreign direct investment; Income distribution; Income classes; Multilevel analysis